The Influence of Customer Experience on Intention to Reuse QRIS with Perceived Ease of Use and Perceived Usefulness as Intervening Variables - Dhewi Ratnasari; Adijati Utaminingsih; DC. Kuswardani (Dinasti Publisher, 2024)
This research aims to analyze the influence of customer experience on the intention to reuse QRIS, with perceived ease of use and perceived usefulness serving as intervening variables. The study sample consists of 96 respondents, selected using the saturated sampling method or census research method. Data was collected through questionnaires and analyzed using SmartPLS software. The results indicate that customer experience does not have a positive and significant effect on perceived usefulness. However, customer experience, when mediated by perceived ease of use and perceived usefulness, significantly influences the intention to reuse QRIS among Trans Semarang service users.